ATTITUDES AND BEHAVIOR IN THE URBAN VILLAGE COMMUNITY RIMBO KALUANG ISSUES FACING THE EARTHQUAKE AND TSUNAMI IN PADANG - YANI, MARDA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Despica, S.Pd., M.Si, Rika (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â This study aims to obtain data, information and an overview of public attitudes in the face of the issue earthquake and tsunami in Rimbo Kaluang Village Padang views of : 1) attitude and, 2) behavior. This type of research is descriptive. Population residing in the Rimbo Kaluang Village community Padang Barat District totaling 1.019 households. Samples were taken in two ways, the sample areas were taken by purposive sampling technique with consideration of taking an area that has more population and respondent sample is taken with a proportional random sampling technique with a proportion of 10% that the sample of 60 households.The results of the study found that: 1) the attitude of the people in the Rimbo Kaluang Village about earthquake and tsunami risk quite well, meaning peoples attitudes in the face of the earthquake and tsunami risks need to be improved and 2) Public behavior in the face of the earthquake and tsunami in the Rimbo Kaluang village good enough, means that peoples behavior in the face of the earthquake and tsunami risks need to be repaired